Representation of Journalists' Professionalism in the Film a Taxi Driver - Maulidia Azwini Anzar; Kadek Dristiana Dwiviyani; Kheyene Molekandella Boer (Publikasi Indonesia, 2024)
Film is a mass communication medium that combines audio, visuals, and narration to convey stories, and information, and serves as a medium of entertainment and education for the audience. One such film that provides both entertainment and historical education is A Taxi Driver, which falls under the genres of drama, history, and politics. This film is based on the true story of a taxi driver who inadvertently became involved in the Gwangju uprising of 1980 after helping a German journalist cover the events in Gwangju. The purpose of this research is to understand the representation of journalistic professionalism in the film A Taxi Driver according to the Code of Ethics of the International Federation of Journalists (IFJ) using a descriptive qualitative research method with Roland Barthes' semiotic analysis. The results of this study identify several scenes in the film A Taxi Driver that illustrate the articles of the International Federation of Journalists (IFJ) Code of Ethics through various actions of Peter, who plays the journalist. Among them: Article 1